2022
DOI: 10.3390/foods11142151
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Effect of the Instant Controlled Pressure Drop Technology (DIC) on Drying and Rehydration Kinetics of Maize Kernels (Zea mays L.)

Abstract: Maize is one of the three worldwide cereal crops with the most outstanding production; however, its postharvest losses range from 2 to 40% due to inadequate harvesting, drying, and storage technologies. This study focuses on the Instant Controlled Pressure Drop technology (DIC) effect on maize kernels’ drying and rehydration kinetics. In total, 19 different DIC treatments were carried out on maize kernels (~25% d.b.). The DIC parameters studied were steam pressure (0.1 to 0.4 MPa) and treatment time (10 to 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Moisture content acts on the heat and mass transfer process during kernel drying, and is related to kernel drying effectiveness and breakage rate, and kernels of corn with high moisture content undergo greater volume changes during drying, and are more susceptible to breakage due to water dissipation and kernel crumpling [103,104]. In addition, the components of the corn kernel, such as the pericarp, hard endosperm, soft endosperm, and germ, have different water dissipation efficiencies, and it has been found that differences in changes in the moisture content of the internal structure of the corn kernel under the same drying conditions can trigger a moisture gradient and create stresses that can crack when the destructive strength of the corn kernel is exceeded [105][106][107]. The effect of temperature gradients during drying can also lead to corn kernel breakage, and temperature gradients caused by non-uniform drying environments or non-consistent drying rates can cause kernel cracking during drying [97], with temperature gradients typically arising within approximately 20 seconds after the start of drying and disappearing after 2 to 3 minutes [97,108].…”
Section: /13mentioning
confidence: 99%
“…Moisture content acts on the heat and mass transfer process during kernel drying, and is related to kernel drying effectiveness and breakage rate, and kernels of corn with high moisture content undergo greater volume changes during drying, and are more susceptible to breakage due to water dissipation and kernel crumpling [103,104]. In addition, the components of the corn kernel, such as the pericarp, hard endosperm, soft endosperm, and germ, have different water dissipation efficiencies, and it has been found that differences in changes in the moisture content of the internal structure of the corn kernel under the same drying conditions can trigger a moisture gradient and create stresses that can crack when the destructive strength of the corn kernel is exceeded [105][106][107]. The effect of temperature gradients during drying can also lead to corn kernel breakage, and temperature gradients caused by non-uniform drying environments or non-consistent drying rates can cause kernel cracking during drying [97], with temperature gradients typically arising within approximately 20 seconds after the start of drying and disappearing after 2 to 3 minutes [97,108].…”
Section: /13mentioning
confidence: 99%
“…El contenido de humedad para la cinética de secado de maíz inicial fue de 22,13%, cada muestra finalizo con un contenido de humedad de 0,53%; 0,7%; 0,61%. Según Cardador-Martínez et al, 13 realiza la cinética de secado por un lapso de 24 h con la diferencia que el peso se registra cada 5 min durante los primeros 30 min, luego a los 45, 60, 90, 120, 150 y 180 min. Hasta lograr que el contenido de agua de equilibrio.…”
Section: Cinética De Secadounclassified
“…Maize (Zea mays L.) is a significant cereal crop and has the most abundant worldwide production, supplying human nutrition, animal feed, and feedstock for many industrial products and biofuels [1]. In addition to outstanding progress in the selection of new maize genotypes, the potential of maize yield is largely affected by abiotic and biotic factors, themselves determined by a certain combination of different factors, such as soil and climatic conditions, solar radiation, quality of seed, genetic performance, the potential for hybrids, and field management practices [2][3][4].…”
Section: Introductionmentioning
confidence: 99%